Предмет: Физика,
автор: mrat00
a=4-j2
b=5+j5
Найти a*b a+b
Ответы
Автор ответа:
0
Преобразуем выражения
а = 2(2-j)
b = 5(1+j)
a*b = 10(2-j)(1+j)= 10(2+2j-j-j^2)= 10(-j^2+j+2)
a + b = 4-2j + 5 + 5j = 9 + 3j = 3(3+j)
а = 2(2-j)
b = 5(1+j)
a*b = 10(2-j)(1+j)= 10(2+2j-j-j^2)= 10(-j^2+j+2)
a + b = 4-2j + 5 + 5j = 9 + 3j = 3(3+j)
Похожие вопросы
Предмет: Химия,
автор: zaborinka123
Предмет: Алгебра,
автор: nastadedova882
Предмет: Русский язык,
автор: nikfomin21
Предмет: Математика,
автор: лерунчик4
Предмет: Математика,
автор: Verinit